Görsel göstergebilimde reklam fotoğrafının yeri - Batumoğlu, Pınar Ceylan (My University, 2013)
Bu çalışmada; göstergebilimin tanımı ve tarihçesi incelenip, gösterge ve fotoğraf ilişkisi alt başlıklar halinde irdelenmiştir. Göstergebiliminin, temel kavramları araştırılıp, aktarılmıştır. Reklam fotoğrafının tanımı ve tarihçesi anlatılarak başarılı bir reklam fotoğrafını oluşturan anlatım dilinin temel öğeleri üzerinde durulmuştur. Görsel göstergebilim ile reklam fotoğrafı arasındaki ilişki, tarih ve fotoğraf örnekleri incelenerek, çözümlenmiştir. Böylece insan algısının isimlendirme yetisini inceleyen göstergebilimin, reklam fotoğrafı üzerindeki etkisi sorgulanarak, değerlendirme yapılmıştır. rsel göstergebilim, Reklam fotoğrafı, Gösterge.

In this dissertation, the description and the history of the semiotics are analyzed along with “meaning” and “perception” as its sub-divisions. Visual semiotics is examined together with its main conception as another sub-division. This paper focuses on main features of the language that composes the attractive advertisement photo while framing the history of advertisement photo. The relationship between visual semiotics and advertisement photo is evaluated based on analysis made on history and sample photographs. In this way the effect of visual semiotics on advertisement photo that assesses the naming ability of human perception is measured. Key Words: Visual semiotic, Advertisement photography, semiotic.
Keywords: Fotoğrafçılık